2016
DOI: 10.1109/tcsii.2015.2483218
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in a Single Op-Amp–Based Jerk Circuit: Experiments and Simulations

Abstract: We report a five-component autonomous chaotic oscillator of jerky type, hitherto the simplest of its kind, using only one operational amplifier. The key component of the circuit is a junction field-effect transistor operating in its triode region, which provides a nonlinear resistor of antisymmetrical current-voltage characteristic, emulating a Colpitts-like chaotic circuit. We describe the experimental results illustrating the dynamical behavior of the circuit. In addition, we report numerical simulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…The first advantage is much better than that of the simplest chaotic flow, whose circuit implementation will inevitably require more than 5 electronic components. Not only are the second and third advantages remarkably comparable to the simplest chaotic flow, but they also circumvent the 2 existing disadvantages in Tchitnga et al…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The first advantage is much better than that of the simplest chaotic flow, whose circuit implementation will inevitably require more than 5 electronic components. Not only are the second and third advantages remarkably comparable to the simplest chaotic flow, but they also circumvent the 2 existing disadvantages in Tchitnga et al…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, circuit I in Figure A appears to be a slightly modified version of the existing 6‐term 2‐nonlinearity circuit in Tchitnga et al, ie, the gate of the JFET of circuit I is connected to node m , as shown in Figure A, whereas the gate of the JFET of Tchitnga et al, was differently connected to node n of Figure A, (the connection is not shown here). Although such a modification does not significantly alter the state equations of circuit I from those of the existing 6‐term 2‐nonlinearity circuit of Tchitnga et al, it allows circuits I and II to form mirrored images of each other. The term “mirrored” is used in the sense that the 2 positions of L and J of circuits I and II are symmetrically flipped positions to each other around the capacitor C 1 .…”
Section: The Simplest Chaotic Jerk Circuit Through a Twin‐jerk Singlementioning
confidence: 99%
See 2 more Smart Citations
“…And, we also discuss the construction of the chaotic system. Due to its potentiality, chaos has been applied in a lot of applications, for example, in liquid mixers, 22 nonlinear circuits, 23 and especially in secure communication. The first chaotic system was found by Lorenz in his studies on meteorology.…”
Section: D Chaotic System Descriptionmentioning
confidence: 99%